Integration of a robotic arm Lynxmotion to a Robotino Festo through a Raspberry Pi 4 - Diaz, Bryan (2022)
The robotic mobile system Robotino, developed by FESTO, is a robotic platform oriented towards research and education, which is why it has a reduced amount of actuators of limited real functionality. This article proposes the integration of a Raspberry Pi 4 to a Robotino FESTO with the purpose of expanding the number of digital inputs this robot has, in addition to allow the input of analog signals by serving as a communication interface between devices through an ethernet connection. In this way, the installation of robotic arm Lynxmotion AL5 with 5 degrees of freedom to the Robotino through the Raspberry Pi 4 is proposed so that it performs additional functions and applications without interfering with the digital inputs of the Robotino, that are already used by the sensors and accessories installed by default. By establishing the connection between both devices (Robotino and Lynxmotion AL5 robotic arm),a mobile system of 7 degrees of freedom of great versatility will be obtained. Results validation was made with the Robotino View simulation software and through real tests.